Guernsey : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2011)
This report provides a summary of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) measures in place in Guernsey at the time of the mission or shortly thereafter. The assessors reviewed the institutional framework; the relevant AML/CFT laws, regulations, guidelines, and other requirements; and the regulatory and other systems in place to deter and punish money laundering (ML) and the financing of terrorism (FT) through financial institutions and Designated Non-Financial Businesses and Professions (DNFBP). The assessors also examined the capacity, implementation, and effectiveness of all these systems.